Character Analysis of Student Responsibilities After the Implementation of Distance Learning at Elementary School - Dela Ambarsari; Akhtim Wahyuni (AL-ISHLAH: Jurnal Pendidikan, 2022)
The government implemented the online learning system when the Covid-19 pandemic broke out. Online learning impacts the character development of student responsibilities such as discipline in doing assignments on time, carrying out obligations as students, and the ability to cooperate with groups because teachers do not supervise students directly in class. In fact, according to Law Number 20 of 2003 concerning the National Education System, national education aims to shape students' disposition. Responsibility is one characteristic that plays an essential role for students in forming dispositions in school. This study aims to analyze the character of student responsibility during limited face-to-face learning after the Covid-19 pandemic. The subjects in this study were students and homeroom teachers at SDN Kalitengah II Tanggulangin, Sidoarjo. The data collection method is carried out qualitatively. The results of this study show that student responsibilities are well demonstrated by the established indicators of student responsibility character. Further research is expected to be carried out with different types of characters, carried out learning reflections, and coupled with quantitative method validation.